On Hölder and Minkowski Type Inequalities - Petr Chunaev; Ljiljanka Kvesić; Josip Pečarić (Abstract and Applied Analysis)
We obtain inequalities of Hölder and Minkowski type with weights generalizing both the case of weights with alternating signs and the classical case of nonnegative weights.